Breastfeeding and Complementary Feeding are Associated With Cognition and Vision in Rural Ghanaian Infants - Mary Amoako; Fiifi Amoako Atta Panyin Essiam; Kwadwo Owusu Akuffo; Moses Awuni; Samson Darrah; Helena Nti (Reproductive, Female and Child Health)
ABSTRACT Importance Dietary patterns during infancy play a key role in shaping developmental outcomes including vision and cognition in children. Objective This study sought to investigate the association between breastfeeding, complementary feeding patterns and child developmental outcomes including cognition, vision, motor skills, language and socio‐emotional development. Methods This cross‐sectional study recruited two hundred and seventy (270) children aged 6‐23 months from rural areas in the Bosomtwe district through convenience sampling. Data on socio‐demographics, breastfeeding practices, complementary feeding practices and food frequency were collected. Haemoglobin concentration was assessed using standard protocols. Cognition was assessed with the Caregiver Reported Early Development Instruments while visual acuity was assessed with Teller Acuity Cards. Results Two major dietary patterns were identified within the population; Vegetable‐enriched Indigenous Diet (VID) pattern and Milk‐enriched Cereals & infant Formular (MCF) pattern. The VID pattern significantly improved the odds of a better visual acuity (OR = 4.55, 95 CI: 1.62–12.80, p = 0.004) and language skills (OR = 1.90, 95% CI: 1.02–3.54, p = 0.043) whiles the MCF pattern improved the likelihood of good cognition (AOR = 2.00 95% CI: 1.028–3.90, p = 0.041). Continued breastfeeding was significantly associated with good cognition (AOR: 4.30, 95% CI: 2.03–9.14). Interpretation Breastfeeding and Milk‐enriched cereals and Infant formula patterns were associated with cognition. Vegetable‐enriched indigenous pattern improved the odds of visual acuity and language development. Interventions aimed at promoting optimal nutrition and supporting breastfeeding practices could significantly enhance developmental outcomes among children in similar settings.